2021
DOI: 10.3390/molecules26113330
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization and Release Studies of Triazole Derivatives from Grafted Copolymer Based on Gellan-Carrying Betaine Units

Abstract: New polymer-bioactive compound systems were obtained by immobilization of triazole derivatives onto grafted copolymers and grafted copolymers carrying betaine units based on gellan and N-vinylimidazole. For preparation of bioactive compound, two new types of heterocyclic thio-derivatives with different substituents were combined in a single molecule to increase the selectivity of the biological action. The 5-aryl-amino-1,3,4 thiadiazole and 5-mercapto-1,2,4-triazole derivatives, each containing 2-mercapto-benz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In addition, the mechanism of triazole release from PG and PGB1 copolymers is more complex, being controlled by both swelling and diffusion processes. These results demonstrated that the graft copolymer with a betaine structure may be a potential candidate for the development of oral drug delivery systems as tablets or capsules [122].…”
Section: Other Drug Delivery Systemsmentioning
confidence: 76%
See 2 more Smart Citations
“…In addition, the mechanism of triazole release from PG and PGB1 copolymers is more complex, being controlled by both swelling and diffusion processes. These results demonstrated that the graft copolymer with a betaine structure may be a potential candidate for the development of oral drug delivery systems as tablets or capsules [122].…”
Section: Other Drug Delivery Systemsmentioning
confidence: 76%
“…These results demonstrated that the graft copolymer with a betaine structure may be a potential candidate for the development of oral drug delivery systems as tablets or capsules. [122].…”
Section: Other Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enthalpy changes of the reaction Δ H , the Gibbs free energy change Δ G and the entropy change Δ S can be calculated from Van't Hoff equation. 21 ln K 2 / K 1 = Δ H (1/ T 1 − 1/ T 2 )/ R Δ G = Δ H − T Δ S = − RT ln K T is the thermodynamic temperature, R is the gas constant (8.314 J (mol −1 K −1 )); K is the binding constant of TA and BSA at the corresponding temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The enthalpy changes of the reaction DH, the Gibbs free energy change DG and the entropy change DS can be calculated from Van't Hoff equation. 21 ln…”
Section: Calculation Of Thermodynamicsmentioning
confidence: 99%